A behavioural trading strategy in the Singapore stock market. - Chen, Zhang Rui. (2012)
The study by Cooper, Gulen, and Schill [2009] documented a strong negative relation between the growth in firms’ total assets and stock returns, often referred to as the “asset growth effect”. In our study, we seek to explore the asset growth effect in Singapore. Our study indicates that while the U.S. market possesses both price-to-book (P/B) and size effect, we fail to observe a similar phenomenon in Singapore. Our cross-section regression analysis finds no relationship between the variables. This cross-country asset growth variation is a hotly debated topic in finance literature. This phenomenon can be explained by either risk or behavioral based approaches. Cooper, Gulen, and Schill [2009] attributed the asset growth effect in U.S. to over-investment tendency of corporate managers and excessive extrapolation on past growth by investors when valuing firms, hence supporting the behavioral based explanations. We conducted a secondary research and concluded that behavioral based explanations, i.e. asset homogeneity and reliance on internal financing, provide the best explanation for the lack of an asset growth anomaly in Singapore.